Implementation of Merdeka Belajar through Museums as a Learning Resource in Differentiated Project Based History Learning - M. Maman Sumaludin (Universitas Syiah Kuala, 2022)
This study aims to describe the implementation of Merdeka Belajar through museums as a learning resource in differentiated project based history learning in class XII of Social Studies at Senior High School 4 Bandung. This research method uses descriptive qualitative methods with data collection techniques through observation, documentation, interviews and equipped with a questionnaire. The results of the study indicate that: The need to design differentiated project based learning through museum as a learning resource in a systematic and planned; The implementation of differentiated project based learning is carried out in the classroom and visits to the Museum of the Asian African Conference as a learning resource; In practice, the teacher gives students freedom within certain limits to choose the type of project, participation in the work, to the type of social media as a means of publishing student work; The results obtained in project based learning are differentiated, namely students become active, students can find out so they can make works from museums as educational and inspirational learning resources; In addition, teachers can develop the potential of different students through differentiation projects. This research is expected to be an input for further research and can be implemented in differentiated project based learning.